Fisiologia da maturação e metabolismo de parede celular de frutos de acessos de umbuzeiro - Rodrigues, Edileide Natália da Silva (2022)
The umbuzeiro, a native and endemic species of the Brazilian Semiarid, has a fruit with a peculiar and highly appreciated flavor and aroma. Accesses with different characteristics have been selected with a view to potential markets, such as the giant umbus. The harvested fruits show rapid ripening and, therefore, a rapid loss of quality, resulting in a reduced commercialization period. In this sense, studies on cell wall metabolism will provide bases for a better understanding of umbu maturation physiology, allowing the development of actions to delay postharvest softening, making it possible to increase its conservation, expanding consumption, and use. Given the above, the objective of this work was to evaluate the maturation physiology and cell wall metabolism of fruits of umbuzeiro accessions at two maturity stages. Ethylene production, respiratory rate, firmness, total and soluble pectin contentes, and enzyme activities related to fruit softening were evaluated. The design used was completely randomized, in a 4x2 factorial scheme (four accessions, including América Dourada, Lontra, and Macaúbas - these three as giant umbus, and the regional umbu tree occurring in Cuité-PB), in 2 maturity stages (ripe green and mature), in 4 replications. The fruits respiratory patter is typical climacteric, with the ethylene peak preceding that of respiration. The peel color index indicated a transition from green to yellow during maturation for Cuité, Lontra, and Macaúbas accessions, unlike fruitd of the pigmented accession América Dourada. América Dourada access, differed between fruit maturity stages in terms of firmness, which was higher in ripe green fruits, also in the peel showed a reduction in total pectin content and an increase in polygalacturonase activity. The fruit firmness of the accessions América Dourada, Lontra, and Macaúbas at similar maturation stages was approximately 2 times higher than that of the regional Cuité. Fruits of the Lontra accession,due to their higher SS/TA ratio, are suitable for fresh consumption, as they are sweeter, which is preferable to the palate of Brazilian consumers. The progress in thc maturation of Cuité -PB, Lontra, and Macaúbas umbus was characterized by an increase in soluble solids, color index, decrease in titratable acidity, increase in the SS/TA ratio, increase in soluble pectin in the fruit pulp and the consequent fruit softening, resulting in reduced firmness. In the pulp of Lontra and Macalbas giant varieties, a decrease in total pectin was clearly observed in parallel with an increase in the polygalacturonase activity. Together, the study of the respiratory profile coupled with the activity of cell wall pectic metabolism enzymes provides an understanding of the postharvest softening process of Spondias tuberosa fruits.